Using of Bacteria Heterotrophic as an Anti-Bacterial Againts Pathogenic Bacteria Isolated from Sea Water in Dumai City , Riau Province - Dewi Sujani Adithiya; Feliatra '; Afrizal Tanjung (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Heterotrophic bacteria have a role as decomposer of organic compounds (mineralization) and inorganic nitrogen (ammonia, nitrite, and nitrate) derived from industrial waste, decomposition of uneaten feed, faecal, excretion of fish and have the ability to inhibit the growth of pathogenic bacteria. This research was conducted in November untill December 2016. The results of antagonism test showed isolated bacteria have the ability to inhibit the growth of pathogenic bacteria (Vibrio algynolyticus, Aeromonas hydrophila and Pseudomonas sp.) Zone of inhibition in D5, D6 and D4 isolates classified in the strong category with zone of inhibition average of 10.5 to 11.8 mm and zone of inhibition in D1, D2, D3, D5, D7 isolates classified in the medium category with zone of inhibition average of 5.3 to 8.5 mm and each of the isolates are also classified in the weak category. The results of DNA analysis of heterotrophic bacteria isolated from marine waters of industrial area and low salinity of estuarine waters by using the PCR method technique 16S sequences found three strains of bacteria from the highest level of homology Bacillus toyonensis, Bacillus cereus and Bacillus pseudomycoides. D1 isolates has similarity to Bacillus cereus strain ASK16, D2 isolates to Bacillus toyonensis strain AC OPR1150Xg, D3 isolates to Bacillus pseudomycoides strain F1-8, D4 isolates to Bacillus cereus strain SBFW51, D5 isolates to Bacillus cereus strain OPP5 3-2, D6 to Bacillus cereus strain SBFW5S, D7 isolates to Bacillus cereus strain B4. Most of isolated bacteria obtained from the waters of industrial area because it receives much of nutrients that are very influential in the growth of bacteria.Kata Kunci : Bakteri Hetrotrofik, Antagonisme, Sekuens 16S rRNA